Impact of intracellular metallothionein on metal biouptake and partitioning dynamics at bacterial interfaces. Issue 43 (27th October 2017) - Présent, Romain M.; Rotureau, Elise; Billard, Patrick; Pagnout, Christophe; Sohm, Bénédicte; Flayac, Justine; Gley, Renaud; Pinheiro, José P.; Duval, Jérôme F. L.
Abstract : This study reports the quantitative evaluation of the metal biopartitioning dynamics following biouptake at bacterial interfaces with explicit account of the effects stemming from intracellular metal binding by metallothionein proteins. Abstract : Genetically engineered microorganisms are alternatives to physicochemical methods for remediation of metal-contaminated aquifers due to their remarkable bioaccumulation capacities. The design of such biosystems would benefit from the elaboration of a sound quantitative connection between performance in terms of metal removal from aqueous solution and dynamics of the multiscale processes leading to metal biouptake. In this work, this elaboration is reported for Escherichia coli cells modified to overexpress intracellular metallothionein (MTc), a strong proteinaceous metal chelator. Depletion kinetics of Cd(ii ) from bulk solution following biouptake and intracellular accumulation is addressed as a function of cell volume fraction using electroanalytical probes and ligand exchange-based analyses. It is shown that metal biouptake in the absence and presence of MTc is successfully interpreted on the basis of a formalism recently developed for metal partitioning dynamics at biointerfaces with integration of intracellular metal speciation. The analysis demonstrates how fast sequestration of metals by intracellular MTc bypasses metal excretion (efflux) and enhances the rate of metal depletion to an extent such that complete removal is achieved at sufficiently large cell volume fractions. The magnitude of the stability constant of nanoparticulate metal–MTc complexes, as derived from refined analysis of macroscopic bulk metal depletion data, is further confirmed by independent electrochemical measurement of metal binding by purified MTc extracts.